Directed evolution of glutathione transferases towards a selective glutathione-binding site and improved oxidative stability - Axarli, Irine; Muleta, Abdi W.; Chronopoulou, Evangelia G.; Papageorgiou, Anastassios C.; Labrou, Nikolaos E. (Biochimica et biophysica acta. General subjects, 2017)
Glutathione transferases (GSTs) are a family of detoxification enzymes that catalyze the conjugation of glutathione (GSH) to electrophilic compounds. A library of alpha class GSTs was constructed by DNA shuffling using the DNA encoding the human glutathione transferase A1-1 (hGSTA1-1) and the rat glutathione transferase A1-1 (rGSTA1-1). Activity screening of the library allowed the selection of a chimeric enzyme variant (GSTD4) that displayed high affinity towards GSH and GSH-Sepharose affinity adsorbent, higher kcat/Km and improved thermal stability, compared to the parent enzymes. The crystal structures of the GSTD4 enzyme in free form and in complex with GSH were determined to 1.6Å and 2.3Å resolution, respectively. Analysis of the GSTD4 structure showed subtle conformational changes in the GSH-binding site and in electron-sharing network that may contribute to the increased GSH affinity. The shuffled variant GSTD4 was further optimized for improved oxidative stability employing site-saturation mutagenesis. The Cys112Ser mutation confers optimal oxidative stability and kinetic properties in the GSTD4 enzyme. DNA shuffling allowed the creation of a chimeric enzyme variant with improved properties, compared to the parent enzymes. X-ray crystallography shed light on how recombination of a specific segment from homologous GSTA1-1 together with point mutations gives rise to a new functionally competent enzyme with improved binding, catalytic properties and stability. Such an engineered GST would be useful in biotechnology as affinity tool in affinity chromatography as well as a biocatalytic matrix for the construction of biochips or enzyme biosensors. [Display omitted] •GSTs are enzymes involved in the metabolism of xenobiotics.•A GST (GSTD4) was created through DNA shuffling and showed high affinity towards GSH.•The crystal structure of the GSTD4 enzyme was determined.•The GSTD4 enzyme was further optimized for improved oxidative stability.•The GSTD4 enzyme could be useful as affinity and catalytic tool in biotechnology.